User-Focused Mixed Methods Approaches to Assess Collection - White, Hollie; Haddow, Gaby (2018)
Libraries must maximise their acquisitions funding to ensure that the materials in their collections match the particular needs of their users. This is especially important as budgets shrink and an increasing variety of information sources across a range of media are available. In order to manage these competing dynamics, a sustainable and systematic approach to collection assessment is imperative and will provide libraries with data with which to make informed decisions. This paper describes a unique and focused approach to collection assessment that involves mixed methods techniques. It demonstrates how a combination of quantitative and qualitative data sources relating to specific collection items can be used to consider both their statistical and practical significance. To identify the use of these items a range of quantitative data sources are identified, from standard borrower records to COUNTER statistics to Ezproxy logfiles. Alongside these data are the qualitative information gathered through lobby testing, qualitative surveys, and interviews. These qualitative user-experience approaches allow libraries to gain feedback directly from library patrons about collection items, their use, and their value. All approaches described in this paper are vendor and platform neutral that can be implemented in any library type. An overview of the data collection approaches and how to implement these in practice are discussed to enable libraries to adapt the methods to their specific collection assessment needs. The main body of the paper presents several cases, based on three types of collection items: newly acquired, high cost, and low use. The cases incorporate the different methodological approaches and demonstrate how to interpret the results of the assessment in order to reach informed acquisitions and collection management decisions.